PSCA and MUC1 in non-small-cell lung cancer as targets of chimeric antigen receptor T cells. (4th March 2017) - Wei, Xinru; Lai, Yunxin; Li, Jin; Qin, Le; Xu, Youdi; Zhao, Ruocong; Li, Baiheng; Lin, Simiao; Wang, Suna; Wu, Qiting; Liang, Qiubin; Peng, Muyun; et al.
ABSTRACT: In recent years, immunotherapies, such as those involving chimeric antigen receptor (CAR) T cells, have become increasingly promising approaches to non-small-cell lung cancer (NSCLC) treatment. In this study, we explored the antitumor potential of prostate stem cell antigen (PSCA)-redirected CAR T and mucin 1 (MUC1)-redirected CAR T cells in tumor models of NSCLC. First, we generated patient-derived xenograft (PDX) mouse models of human NSCLC that maintained the antigenic profiles of primary tumors. Next, we demonstrated the expression of PSCA and MUC1 in NSCLC, followed by the generation and confirmation of the specificity and efficacy of PSCA- and MUC1-targeting CAR T cells against NSCLC cell lines in vitro . Finally, we demonstrated that PSCA-targeting CAR T cells could efficiently suppress NSCLC tumor growth in PDX mice and synergistically eliminate PSCA + MUC1 + tumors when combined with MUC1-targeting CAR T cells. Taken together, our studies demonstrate that PSCA and MUC1 are both promising CAR T cell targets in NSCLC and that the combinatorial targeting of these antigens could further enhance the antitumor efficacy of CAR T cells.